Clinical caracterization, geoprocessing and genotypic profile of patients with hepatitis C admitted in the 20ª Regional de Saúde of the State of Paraná (Research, Society and Development, 2021)
Hepatitis C is a pathology of viral etiology that competes as one of the main causes of chronic liver disease worldwide. Globally, it is estimated that around 80 million people are carriers of the hepatitis C virus (HCV). In Brazil, the data shows that 2.5% to 4.9% of the population is infected by the virus. Objective: to carry out the clinical characterization, the geoprocessing of the cases and to identify the genotypic profile of patients with hepatitis C admitted by the 20ª Regional de Saúde of the the municipality of Toledo-PR, Brazil. Methodology: epidemiological, retrospective and descriptive study, having as its database the medical records and exams from the 20ª Regional de Saúde of the municipality of Toledo-PR regarding the period from january 2015 to august 2020. Results: among the 137 cases analyzed, there was a predominance of male individuals (58%), with between 56 and 65 years of age (31%), of self-declared white ethnicity (58%) and with incomplete elementary education (43%). The most frequent comorbidity was systemic arterial hypertension (18%). There was a predominance of genotype 1 (46%). Sofosbuvir+Daclatasvir+Ribavirin corresponded to the most used therapeutic regimen (11%). F1 was the most common degree of liver fibrosis (16%). As for the density of cases, the municipality of Toledo led with 46 carriers. Conclusion: the sociodemographic, clinical and genotypic characteristics of patients with hepatitis C vary according to the geographical region and, therefore, the conduct of epidemiological studies should be encouraged.